Implementation of Indonesian Sustainable Palm Oil Certification in Realizing Sustainable Business: A Comparative Study with the European Union Deforestation Regulation - Sabrina, Fadiah Tarisa (Jurnal Locus Penelitian dan Pengabdian, 2025)
This research examines the implementation of the Indonesian Sustainable Palm Oil (ISPO) certification in promoting sustainable palm oil business practices in Indonesia, through a comparative study with the European Union Deforestation Regulation (EUDR). The background of this study stems from the strategic role of palm oil as a major national commodity that significantly contributes to the economy yet faces sustainability challenges. The ISPO certification is intended to ensure business practices that are legal, environmentally friendly, and socially equitable. However, there are still gaps in its implementation, especially in meeting the stringent standards of the EUDR, which requires for products that exports to the European Union. This study aims to analyze the legal framework of ISPO in promoting sustainable business practices and to identify the legal implications arising from the differences in standards between ISPO and the EUDR, particularly in terms of legal certainty and global market access for Indonesian businesses. The research adopts a normative juridical approach with qualitative analysis of national and international regulations, as well as relevant literature studies. The results of this research are expected to provide more effective and inclusive policy recommendations, strengthen international recognition of the ISPO, and protect the interests of smallholder farmers and local communities within Indonesia’s palm oil supply chain amid evolving global regulatory dynamics.